2017
DOI: 10.1108/jbs-02-2016-0015
|View full text |Cite
|
Sign up to set email alerts
|

Social media: open innovation in SMEs finds new support

Abstract: Purpose The exchange of knowledge in social networks is fundamental to innovation. Open, interactive, innovation requires collaboration through social networks. This social networking is increasingly carried out across the Internet through social media applications. The purpose of this study is to explore the use of social media in open innovation, and explain how this practice is carried out in small and medium-sized enterprises (SMEs). With less resources than large firms, SMEs both have a greater need for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 11 publications
1
39
0
2
Order By: Relevance
“…The publication trend has grown steadily since, reaching a maximum of twelve publications in 2018. Among 45 articles, the recent ones are from 2017 (Amidi et al, 2017;Edwards et al, 2017;Hitchen et al, 2017;Okazaki et al, 2017;Panda & Deepa, 2017;Shen & Guangyan, 2017; Soto-Acosta & Palacios-Marques, 2017; Świgoń, 2017), 2018 (Chang, 2018;Das & Mahapatra, 2018;Esin, 2018;Hood, 2018;Kumi & Sabherwal, 2018;Lu, Zhou, & Chen, 2018;Park & Gabbard, 2018;Sedighehm & Ainin, 2018;Septiani & Ave, 2018;Zhang, Liu, Deng, & Chen, 2018) and 2019 (Nisar, Prabhakar, & Strakova, 2019;Tayebi, Manesh, Khalili, & Sadi-Nezhad, 2019;Kim, Gibbs, & Scott, 2019 etc. ) The rising trend indicates a growing interest in the field of knowledge sharing on social media, but also its infancy.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The publication trend has grown steadily since, reaching a maximum of twelve publications in 2018. Among 45 articles, the recent ones are from 2017 (Amidi et al, 2017;Edwards et al, 2017;Hitchen et al, 2017;Okazaki et al, 2017;Panda & Deepa, 2017;Shen & Guangyan, 2017; Soto-Acosta & Palacios-Marques, 2017; Świgoń, 2017), 2018 (Chang, 2018;Das & Mahapatra, 2018;Esin, 2018;Hood, 2018;Kumi & Sabherwal, 2018;Lu, Zhou, & Chen, 2018;Park & Gabbard, 2018;Sedighehm & Ainin, 2018;Septiani & Ave, 2018;Zhang, Liu, Deng, & Chen, 2018) and 2019 (Nisar, Prabhakar, & Strakova, 2019;Tayebi, Manesh, Khalili, & Sadi-Nezhad, 2019;Kim, Gibbs, & Scott, 2019 etc. ) The rising trend indicates a growing interest in the field of knowledge sharing on social media, but also its infancy.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Some authors are skeptical and believe that social media limits knowledge sharing (Gibbs & Eisenberg, 2013). On the contrary, positive approaches emphasize how social sites empower innovation through knowledge sharing (Hitchen et al, 2017) or present this channel as the future of the knowledge sharing practices (Majchrzak et al, 2013). Following the positive point of view, Sirous and Watson-Patridge (2016) concluded that social media presents a venue with evergrowing significance, for both individuals and organizations, as it greatly enhances sharing of tacit knowledge.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study investigates whether the valuations results of unlisted stocks in the TPKS affect taxpayers' repurchase price. To verify the research question, the research model is set similar to Equations (5) and (6). Equation (5) is a research model to verify a difference in pricing the unlisted stocks in the TPKS between the tax authority and taxpayers (SMEs).…”
Section: Research Modelmentioning
confidence: 99%
“…By contrast, the fair value of listed stock can be identified because the stocks are traded in the stock market (with stock market price). The fair value of unlisted stocks cannot be easily identified because an active market for these stocks does not exist [6]. Ohlson [7] argues that a linear relationship exists between accounting information and firm value, and, thus, the unlisted stocks' value can be estimated using accounting information of the current unlisted corporation.…”
Section: Introductionmentioning
confidence: 99%